2022
DOI: 10.1186/s13089-022-00285-3
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the diagnostic accuracy of lung ultrasound for pulmonary embolism in patients with and without pleuritic chest pain

Abstract: Background Lung ultrasound (LUS) has a role in the diagnosis of pulmonary embolism (PE) mainly based on the visualization of pulmonary infarctions. However, examining the whole chest to detect small peripheral infarctions by LUS may be challenging. Pleuritic pain, a frequent presenting symptom in patients with PE, is usually localized in a restricted chest area identified by the patient itself. Our hypothesis is that sensitivity of LUS for PE in patients with pleuritic chest pain may be higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Small infarctions are often visible by lung ultrasound and invisible by chest radiography. The higher sensitivity of ultrasound is particularly impactful in the first diagnosis of patients with mild symptoms but active acute pleuritic pain [ 13 ]. Thus, lung ultrasound implementation in emergency is bringing to an increase of mild pauci-symptomatic patients showing the typical sonographic infarction, then confirmed by multirow angio-CT as small subsegmental embolisms.…”
Section: Textmentioning
confidence: 99%
“…Small infarctions are often visible by lung ultrasound and invisible by chest radiography. The higher sensitivity of ultrasound is particularly impactful in the first diagnosis of patients with mild symptoms but active acute pleuritic pain [ 13 ]. Thus, lung ultrasound implementation in emergency is bringing to an increase of mild pauci-symptomatic patients showing the typical sonographic infarction, then confirmed by multirow angio-CT as small subsegmental embolisms.…”
Section: Textmentioning
confidence: 99%
“…17 Data in the literature have demonstrated how simultaneously running several evaluations, in addition to clinical risk stratification, may increase diagnostic accuracy. 18 The definitive diagnosis is established by CTPA, or alternatively by scintigraphy or angiography.…”
Section: Basics Of Lung Ultrasoundmentioning
confidence: 99%
“…Systematic reviews demonstrate that LUS has a better diagnostic accuracy than chest X-ray, to detect lung consolidations, pleural effusion, pneumothorax, interstitial syndrome, and lung contusions [27,28 ▪ ]. A recent study has also reported that, by excluding the presence of pulmonary infarction, LUS provides useful information to rule out the suspicious of pulmonary embolism in patients with pleuritic chest pain (sensitivity 81.5% and specificity 95.4%), whereas in patients without pleuritic chest pain the sensitivity drops to 49.5% [29]. Therefore, LUS is a valid alternative to chest X-ray, not only for cost reduction, but also for diagnostic accuracy (Fig.…”
Section: Lung Ultrasonography Diagnostic Accuracy and Patients’ Outcomesmentioning
confidence: 99%